PENGARUH INTEGRITAS IMPLEMENTASI KEBIJAKAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PEMBUATAN KARTU TANDA PENDUDUK ELEKTRONIK - Sabaruddin; Syamsul Alam; Tora Akadira (Halu Oleo University, 2024)
The Civil Registration and Population Office of Central Buton Regency has implemented population policies and provided electronic identity card services based on directives from the central government. This study aims to analyze the impact of implementation integrity and service quality on public satisfaction in the process of obtaining electronic identity cards. The research uses a quantitative method, with primary data as the main source of information. The research strategy employed is a survey involving 248 randomly selected samples. The data analysis technique used is inferential statistical analysis with multiple linear regression procedures in IBM SPSS Statistics version 26.0. From the unstandardized coefficients of the constant (intercept), implementation integrity (X1), and service quality (X2), a multiple regression equation can be formulated as Y=3.267+0.219⋅X1+0.232⋅X2. Individually, both implementation integrity and service quality positively affect public satisfaction. Simultaneously, these two variables influence public satisfaction in the process of obtaining electronic identity cards by 27.2%, while the remaining 72.8% is influenced by other factors not included in the research model.